2012
DOI: 10.1155/2012/125814
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience Using Vitamin D and Analogs in the Treatment of Myelodysplasia and Acute Myeloid Leukemia: A Review of the Literature

Abstract: Despite progress in understanding the biology of acute myeloid leukemia (AML), and despite advances in treatment, the majority of patients with AML die from the disease. The observation that Vitamin D can induce AML blast cells in vitro to differentiate along the monocytic lineage was made 30 years ago; however, it remains to translate this into a clinically meaningful strategy. This is a review of published clinical experience regarding the use of Vitamin D and its analogs, either alone or in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
(26 reference statements)
2
33
0
Order By: Relevance
“…Considering these findings, it is plausible that the patient's leukemic clone co-opted the vitamin D pathway to enhance leukemic cell proliferation without impacting on differentiation. Whether utilising vitamin D or its derivatives in the treatment of AML (as previously reported [8]) may in actuality, enhance leukemia cell proliferation in some AML cases is pure conjecture, but our case highlights that the molecular heterogeneity of AML can now also be extended to vitamin D metabolism.…”
Section: Discussion/conclusionsupporting
confidence: 51%
See 1 more Smart Citation
“…Considering these findings, it is plausible that the patient's leukemic clone co-opted the vitamin D pathway to enhance leukemic cell proliferation without impacting on differentiation. Whether utilising vitamin D or its derivatives in the treatment of AML (as previously reported [8]) may in actuality, enhance leukemia cell proliferation in some AML cases is pure conjecture, but our case highlights that the molecular heterogeneity of AML can now also be extended to vitamin D metabolism.…”
Section: Discussion/conclusionsupporting
confidence: 51%
“…Indeed, previous experiments have demonstrated that vitamin D treatment can induce monocytic differentiation of leukemic precursors [7]. Predicated on these preclinical data and the success of all-trans-retinoic acid differentiation therapy for acute promyelocytic leukemia (APML), non-APML AML cases have also been treated with vitamin D and analogues, but with limited success [8]. In the aforementioned context, it is not obviously clear why up-regulation of the vitamin D pathway would be advantageous to this patient's leukemic blasts.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Overexpression of p21 and HOXA10 facilitates the differentiation of U937 cells into monocytes/macrophages cell lineage (Kim et al, 2012;Rots et al, 1998). Therefore, the therapeutic strategies currently available in the clinical treatment of leukemias and MDS include agents that induce differentiation of hematopoietic precursors (Harrison & Bershadskiy, 2012;Kim et al, 2012;Nagpal et al, 2005;Shanafelt et al, 2011). The main hematologic responses were observed in patients with MDS treated with calcitriol and alfacalcidol (Kim et al, 2012;Mellibovsky et al, 1998).…”
Section: Effects Of Vitamin D On Hematological Malignanciesmentioning
confidence: 99%
“…However, recent clinical trials of vitamin D derivatives (VDDs) showed unremarkable results, suggesting that approaches to the application of this knowledge to the clinic are currently sub-optimal, as recently articulated [1]. In addition to the problems cited in that review, it is also difficult to obviate the hypercalcemic effect of VDDs, the principal cause of patient toxicity [2, 3]. Repeated attempts to synthesize and clinically test analogs of calcitriol, in which the hypercalcemic activity of the analog is dissociated from its differentiation-inducing activity, have as yet produced no tangible results [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the problems cited in that review, it is also difficult to obviate the hypercalcemic effect of VDDs, the principal cause of patient toxicity [2, 3]. Repeated attempts to synthesize and clinically test analogs of calcitriol, in which the hypercalcemic activity of the analog is dissociated from its differentiation-inducing activity, have as yet produced no tangible results [3, 4]. An alternative approach to improve AML therapy is to combine VDDs, including calcitriol, with other compounds.…”
Section: Introductionmentioning
confidence: 99%